JURIDICAL ANALYSIS OF THE ROLE OF POLRI IN DISCOVERING THE CIRCULATION OF NARCOTICS IN THE LEGAL AREA OF THE RIAU ISLANDS (Research Study at Barelang Police) - Trio AD, Alex; Dahlan, Dahlan; Nofrial, Ramon (RADJA PUBLIKA, 2023)
The role of the Narcotics Unit in eradicating and overcoming narcotics abuse is quite large because most of their main tasks and functions have been realized and the Narcotics Unit and the Police should increase legal awareness regarding Prevention, Eradication of Drug Abuse and Illicit Trafficking (P4GN) for the community with outreach and legal counseling, talk shows , screening of films, distribution of stickers/pamphlets on legal sanctions, increasing operational costs by submitting funds to the Regional Police Chief taking into account the existing problems and the amount of funds used for the eradication and control of narcotics crimes in the jurisdiction of the Riau Archipelago so that the eradication and control of narcotics in the Archipelago region Riau can be implemented well.